PENGEMBANGAN APLIKASI MOBILE LEARNING FISIKA SEBAGAI MEDIA PEMBELAJARAN PENDUKUNG - Gunawan, Indra (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2014)
Abstract: The objective of this research is to create a supporting instructional media in the form of mobile learning of main material for Senior Secondary School students. The created mobile learning was played on mobile phone that supports flash player, mainly Symbian S60 3rd based mobile phone. The method applied in this research was research and development. The first step was limited to the material of heat transfer. The trial of an application was conducted to 2 specialized lecturers, 2 media experts, 2 Physics teachers of Senior Secondary School, and 44 students of Al- Azhar Senior Secondary School, Bandar Lampung. Indicators used to assess the created instructional media were the appropriateness of the content to the purpose, appropriateness of instruction to the technical quality. Marks of the three indicators were above 80% so that the created mobile learning was categorized as very good. Based on the findings, it may be concludedthat the instructional media in the form of mobile learning can be used as a supporting instructional media for Senior Secondary School students to learn Physics subject. Keywords: instructional media, mobile learning, heat transfer, physic subject, and Senior Secondary School.